Answer:
cos B = ![\frac{7}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B25%7D)
tan B = ![\frac{24}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B24%7D%7B7%7D)
sin B = ![\frac{24}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B24%7D%7B25%7D)
Step-by-step explanation:
In the right triangle, there are three sides and 2 acute angles
- Hypotenuse ⇒ the opposite side of the right angle
- Leg1 and Leg 2 ⇒ the sides of the right angle
The trigonometry functions of one of the acute angles Ф are
- sin Ф = opposite leg/hypotenuse
- cos Ф = adjacent leg/hypotenuse
- tan Ф = opposite leg/adjacent leg
In Δ ACB
∵ ∠C is the right angle
∴ AB is the hypotenuse
∵ AC is the opposite side of ∠B ⇒ leg1
∵ CB is the adjacent side of ∠B ⇒ leg2
→ By using the ratios above
∴ cos B =
, tan B =
, sin B = ![\frac{AC}{AB}](https://tex.z-dn.net/?f=%5Cfrac%7BAC%7D%7BAB%7D)
∵ CB = 7, AB = 25, AC = 24
∴ cos B = ![\frac{7}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B25%7D)
∴ tan B = ![\frac{24}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B24%7D%7B7%7D)
∴ sin B = ![\frac{24}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B24%7D%7B25%7D)
Answer: 1/3^4 or 1 over 3 fourths beacuse you need to just flip it to get the exponent to be positive. 3^-4 is basically 3^-4 over 1.
Step-by-step explanation:
I'd suggest using "elimination by addition and subtraction" here, altho' there are other approaches (such as matrices, substitution, etc.).
Note that if you add the 3rd equation to the second, the x terms cancel out, and you are left with the system
- y + 3z = -2
y + z = -2
-----------------
4z = -4, so z = -1.
Next, multiply the 3rd equation by 2: You'll get -2x + 2y + 2z = -2.
Add this result to the first equation. The 2x terms will cancel, leaving you with the system
2y + 2z = -2
y + z = 4
This would be a good time to subst. -1 for z. We then get:
-2y - 2 = -2. Then y must be 0. y = 0.
Now subst. -1 for z and 0 for y in any of the original equations.
For example, x - (-1) + 3(0) = -2, so x + 1 = -2, or x = -3.
Then a tentative solution is (-3, -1, 0).
It's very important that you ensure that this satisfies all 3 of the originale quations.
Answer:
Step-by-step explanation:
If by opposite you mean...
1 opposite is -1
If so then its 0 because any rational number and its reciprocal is always 0 its math crazy stuff